Social isolation induces autophagy in the mouse mammary gland: link to increased mammary cancer risk. Issue 10 (October 2016) - Sumis, Allison; Cook, Katherine L; Andrade, Fabia O; Hu, Rong; Kidney, Emma; Zhang, Xiyuan; Kim, Dominic; Carney, Elissa; Nguyen, Nguyen; Yu, Wei; Bouker, Kerrie B; Cruz, Idalia; et al.
Abstract : Social isolation is a strong predictor of early all-cause mortality and consistently increases breast cancer risk in both women and animal models. Because social isolation increases body weight, we compared its effects to those caused by a consumption of obesity-inducing diet (OID) in C57BL/6 mice. Social isolation and OID impaired insulin and glucose sensitivity. In socially isolated, OID-fed mice (I-OID), insulin resistance was linked to reduced Pparg expression and increased neuropeptide Y levels, but in group-housed OID fed mice (G-OID), it was linked to increased leptin and reduced adiponectin levels, indicating that the pathways leading to insulin resistance are different. Carcinogen-induced mammary tumorigenesis was significantly higher in I-OID mice than in the other groups, but cancer risk was also increased in socially isolated, control diet-fed mice (I-C) and G-OID mice compared with that in controls. Unfolded protein response (UPR) signaling (GRP78; IRE1) was upregulated in the mammary glands of OID-fed mice, but not in control diet-fed, socially isolated I-C mice. In contrast, expression of BECLIN1, ATG7 and LC3II were increased, and p62 was downregulated by social isolation, indicating increased autophagy. In the mammary glands of socially isolated mice, but not in G-OID mice, mRNA expressions of p53 and the p53-regulated autophagy inducer Dram1 were upregulated, and nuclear p53 staining was strong. Our findings further indicated that autophagy and tumorigenesis were not increased in Atg7 +/− mice kept in social isolation and fed OID. Thus, social isolation may increase breast cancer risk by inducing autophagy, independent of changes in body weight.